GENDER-INCLUSIVE POLICIES AND THEIR IMPACT ON SUSTAINABLE ECONOMIC GROWTH IN ABUJA, NIGERIA - Okoli, Theresa Omang; Amehojo , Daniel (University of Nigeria Journal of Political Economy, 2025)
Gender inclusivity is vital for sustainable economic growth, especially in developing urban centers like Abuja, Nigeria. This study examines how gender-inclusive policies drive economic development and reduce disparities in employment, entrepreneurship, leadership, and financial access. It evaluates government initiatives, legal frameworks, and private sector interventions promoting gender equity. Despite policy advancements, gender disparities persist due to socio-cultural norms, legal constraints, and institutional inefficiencies. Challenges include weak policy implementation, limited financial support for women-led enterprises, and gender biases in leadership. Through policy analysis, stakeholder interviews, and economic impact assessments, the study explores how gender inclusion enhances productivity, reduces poverty, and supports sustainable development goals (SDGs). Findings indicate that stronger gender policies boost labor force participation, business innovation, and economic resilience. The study recommends that the Federal government should enforce gender-friendly workplace policies, such as equal pay, parental leave, and flexible work arrangements, to further increase female labour force participation, also that financial institutions should expand access to gender-responsive funding, including grants and micro-loans, to support business growth and innovation among female entrepreneurs.